Extremist religious philosophy : the religious doctrines of Satmar Rebbe - Kadosh, Refael (Kaplan Centre for Jewish Studies, 2014)
Rabbi Yoel Teitelbaum, The Satmar Rebbe, (1886-1978) was a well known Hassidic rabbinical leader of the 20th century. He was born into a rabbinical 'dynasty' and was ordained as a rabbi, Rosh Yeshiva and Rebbe in Hungary at a young age. It was in Hungary that his anti-Zionist views were developed. Notwithstanding the annihilation of Eastern European Jewry during the Holocaust, these views became more extreme with the passing years, and in some of his writings he explained the Shoa as a punishment from G-d for the "Zionist sin". The dissertation investigates the Rebbe's writings, which include: his biblical commentary, letters, speeches and sermons, hallachic responsa and philosophical contemplations; with special attention to his most famous book: "Vayoel Moshe".